2013
DOI: 10.2138/am.2013.4470
|View full text |Cite
|
Sign up to set email alerts
|

Cubic perovskite polymorph of strontium metasilicate at high pressures

Abstract: By using a diamond-anvil cell (DAC) with laser heating technology, a cubic perovskite polymorph of SrSiO 3 has been synthesized at ∼38 GPa and 1500-2000 K for the first time. The P-V data of this new phase give ambient temperate elastic constants of V 0 = 49.18(5) Å 3 , K 0 = 211(3) GPa, respectively, when they are fitted against the Birch-Murnaghan equation of state with a fixed K 0 ′ at 4. On decompression, the SrSiO 3 cubic perovskite phase becomes unstable at ∼6.2 GPa and disappears completely at ∼4.7 GPa.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…, Sr 2+ , and Ba 2+ cations are stabilized as hexagonal and/or cubic forms under high pressure [34][35][36][37][38]. These transformations have been confirmed by high-pressure experiments.…”
Section: +supporting
confidence: 53%
See 1 more Smart Citation
“…, Sr 2+ , and Ba 2+ cations are stabilized as hexagonal and/or cubic forms under high pressure [34][35][36][37][38]. These transformations have been confirmed by high-pressure experiments.…”
Section: +supporting
confidence: 53%
“…Therefore, expansion of the A-site cations disrupts the framework and makes the structure amorphous. Amorphization of the cubic perovskite structure has also been observed for SrSiO 3 [38] and BaSiO 3 [46]. Considering the structural similarity, the hexagonal perovskite structures could become amorphous during decompression.…”
Section: Amorphization Under Decompression At Room Temperaturementioning
confidence: 74%
“…Experimental studies of phase transitions in minerals with perovskite-type structures continue to attract considerable attention due to their importance for the understanding of behavior of mineral matter subjected to the effects of high temperature and pressure in the deep Earth geospheres (Xiao et al 2012(Xiao et al , 2013Knight et al 2014Knight et al , 2015. A particular class of perovskite-related materials are antiperovskites, where cations and anions are interchanged so that perovskite-type units are built from anion-centered instead of cation-centered octahedra (Mitchell 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Cubic perovskites (ABO3) have been studied extensively in the last two decades. For example, Xiao et al [6] reported lattice parameters between 3.50 and 3.61 Å for SrSiO3. Tariq et al [7] theoretically computed lattice parameters between 3.80 and 3.85 Å for cubic perovskites of SrAO3 (A = Cr, Fe, and Co).…”
Section: Introductionmentioning
confidence: 99%